Expansion enhanced nanoscopy. Issue 37 (18th September 2018) - Li, Rongqin; Chen, Xuanze; Lin, Zixi; Wang, Yao; Sun, Yujie
Abstract : We developed new strategies to retain and increase the labeling density of expanded samples and accomplished expansion enhanced nanoscopy (ExN). Abstract : The advance of optical super-resolution fluorescence microscopy has revolutionized our vision of the subcellular world. Further improvement in the spatial resolution is of great significance for structural and functional investigations. The recently developed expansion microscopy (ExM), which achieves sub-diffraction imaging via physical expansion of the sample, provides a great opportunity for further resolution enhancement of existing optical super-resolution techniques. However, although such combination seems apparent, several technical obstacles, especially the dramatic loss of fluorescence signal during ExM sample preparation, have hampered this goal. In this work, aiming at this challenge, we have developed new strategies to retain and increase the fluorescence of the expanded sample. With the new labeling methods, we have successfully made the labeling density of expanded samples sufficing the Nyquist sampling criteria for optical super-resolution imaging, such as stimulated emission depletion microscopy (STED) and super-resolution optical fluctuation imaging (SOFI). The newly developed expansion nanoscopic imaging (ExN) approaches, i.e. ExSTED and ExSOFI, demonstrated up to 4-fold resolution enhancement compared to standard STED and SOFI, providing a simple and effective way to realize high resolution imaging both at the cellular and tissue level.